The ante colimote and the visual search for its baroque essence - Ayala García, Patricia (Interpretextos revista semestral de creación y divulgación de las humanidades (Colima), 2025)
The ante colimote, a traditional pastry from Colima, Mexico, combines indigenous and European heritage, reflecting the aesthetics and social values of the Baroque. Its elaborate preparation and rich decoration symbolize luxury, exclusivity, and theatricality, characteristics of Baroque art. Historically reserved for the upper classes, its contemporary popularity highlights a potential tension between cultural heritage and economic access. Ante colimote is not just a dessert, but a living manifestation of collective memory and a bridge between European Baroque art and contemporary regional identity.